Enhancing literacy engagement with culturally relevant reading materials for foreign language learners / Auni Batrisyia Suharto ... [et al.] - Suharto, Auni Batrisyia; Megat Abdul Rahim, Puteri Rohani; Anuar, Nuramira; Norafand, Nor Najihah (Universiti Teknologi MARA, Kedah, 2024)
This concept paper delves into the critical realm of literacy engagement among foreign language English learners and its transformative potential when coupled with culturally relevant reading materials. As the global landscape continues to diversify, educational systems are witnessing an increasing presence of linguistically and culturally diverse student populations. Addressing the unique needs of these learners is paramount, particularly in the realm of literacy development. This paper proposes an innovative approach to enhancing literacy engagement by leveraging culturally relevant reading materials that resonate with the lived experiences and backgrounds of second language English learners. Drawing on a multidisciplinary foundation that integrates theories of language acquisition, cultural psychology, and educational pedagogy, this concept paper seeks to underscore the intrinsic connection between cultural identity and literacy engagement. By intertwining culturally resonant narratives, themes, and characters within reading materials, educators can bridge linguistic and cultural gaps, cultivating an enriched learning environment that empowers learners to engage more deeply with the English Language and its literary expressions. Additionally, the concept paper addresses practical considerations for educators, curriculum designers, and policymakers. It delves into the process of selecting and integrating culturally relevant reading materials, suggesting strategies to ensure authenticity, sensitivity, and alignment with educational objectives. Through an exploration of existing research, this paper highlights the positive impact of culturally relevant reading materials on third language learners’ motivation, comprehension, and overall language proficiency. It also delves into the socioemotional dimensions of such engagement, elucidating how culturally imbued content can provide a sense of belonging, thereby fostering a positive attitude towards language learning.